(untitled) (Principles of Medical Toxicology, 2025)
Synopsis Author Mr. Sanat Mahendra Dhoke, PharmD Scholar, Department of Pharmacy Practice, Parul Institute of Pharmacy & Research, Faculty of Pharmacy, Parul University, Vadodara, Gujarat, India Abstract Pediatric toxicology addresses the unique physiological, developmental, and exposure characteristics that differentiate children from adults in toxic emergencies. Age-specific concerns include altered toxicokinetics with greater absorption through immature gastrointestinal tracts and skin, different distribution patterns due to higher body water proportions, underdeveloped hepatic enzyme systems affecting metabolism, and variable elimination capabilities. These factors often increase vulnerability to toxins while producing different clinical manifestations than seen in adults. Exposure patterns change dramatically with development: infants primarily experience caregiver medication errors; toddlers and preschoolers suffer exploratory ingestions of household products, medications, and plants; school-age children face increasing risk from recreational substances and intentional misuse; and adolescents demonstrate adult-pattern exposures including self-harm attempts. Treatment modifications necessitate weight-based dosing calculations, careful fluid management, adjusted decontamination approaches, and antidote adaptations. Children's smaller airways, decreased glycogen reserves, and immature thermoregulation require special consideration during supportive care. Prevention strategies target developmental stage-specific risks through proper storage practices, child-resistant packaging, supervision appropriate to developmental capabilities, and age-appropriate education. Effective management requires understanding these distinctive aspects while recognizing red flags suggesting non-accidental poisoning requiring child protection involvement. Keywords: Pediatric Poisoning, Developmental Toxicology, Accidental Ingestion, Weight-Based Dosing, Child-Resistant Packaging, Toxicokinetic Differences VIEW PDF